Turismo de sol y playa – cultural: modelo de gestión del emprendimiento turístico basado en la imagen del destino Manabí - Barreiro Intriago, Karla Cecilia (2024)
The objective of this research was to design a entrepreneurship management model that allows positioning the image of the destination in the development of sun and beach-cultural tourism in Manabí. The research was mixed and used an analytical and descriptive approach. The methodology was structured in four phases: 1) tourism situational diagnosis of the entrepreneurial sector, which through the use of the characterization sheet and the application of interviews and surveys, the entrepreneurial system in the Manabí destination was characterized and the problems that impede the development of this sector were identified; 2) analysis of tourism demand with the respective sampling through the application of surveys, which allows identifying the study variables that make up the image of the destination; 3) identify the participation of the actors involved in the entrepreneurial environment, determining that a high percentage of them require advice from the management of the key actors, as well as the link to provide information on the regulations, laws and regulations to their optimal functioning, to fulfill this phase the SWOT matrix of those involved and function sheets were used; in 4) and last phase, the entrepreneurship management model was designed based on the image of the destinations under study. The model describes the programs and projects, as well as processes that will allow the measurement and evaluation of tourism indicators for the optimal development of sun and beach-cultural turism in the coastal area of Manabí province.